Transposon telomeres are widely distributed in the Drosophila genus: TART elements in the virilis group - Casacuberta, Elena (The National Academy of Sciences, 2003)
Telomeres of most animals, plants, and unicellular eukaryotes are made up of tandem arrays of repeated DNA sequences produced by the enzyme telomerase. Drosophila melanogaster has an unusual variation on this theme; telomeres consist of tandem arrays of sequences produced by successive transpositions of two non-LTR retrotransposons, HeT-A and TART. To explore the phylogenetic distribution of these variant telomeres, we have looked for TART homologues in a distantly related Drosophila species, virilis. We have found elements that, despite many differences in nucleotide sequence, retain significant amino acid similarity to TART from D. melanogaster. These D. virilis TART elements have features that characterize TART elements in D. melanogaster: (i) they are found in tandem arrays on chromosome ends, (ii) they are not found in euchromatin, and (iii) they produce both sense and antisense transcripts, with the antisense RNA being in excess. The D. virilis TART elements have one surprising feature: both of the ORFs contain long stretches of the trinucleotide repeat CAX, encoding polyglutamine (with a few interspersed histidines). These long polyglutamine stretches are conserved in the three D. virilis elements sequenced. They do not interrupt any domains of known function in the TART proteins and are not seen in TART proteins from other species. Comparison of the D. virilis and D. melanogaster telomeres suggests that the retrotransposon mechanism of telomere maintenance may have arisen before the separation of the genus Drosophila.